1984
DOI: 10.1161/01.cir.70.6.966
|View full text |Cite
|
Sign up to set email alerts
|

Right ventricular and right atrial collapse in patients with cardiac tamponade--a combined echocardiographic and hemodynamic study.

Abstract: To determine the hemodynamic derangement associated with right ventricular diastolic collapse and to assess the value of right ventricular and right atrial collapse in identifying cardiac tamponade, two-dimensional echocardiograms were recorded simultaneously with measurement of right atrial, pulmonary capillary wedge, intrapericardial, and systemic arterial pressures and cardiac output in 16 patients as they underwent pericardiocentesis. Twelve patients (group I) had evidence of right ventricular or right atr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
65
0
2

Year Published

1985
1985
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 254 publications
(71 citation statements)
references
References 11 publications
4
65
0
2
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][13][14][15] The present study demonstrates distinctive hemodynamic features and echocardiographic manifestations of experimental cardiac tamponade in the presence of ischemic left ventricular dysfunction. The absence of pulsus paradoxus and the altered manner in which the cardiac chambers are compressed aid our understanding of the pathophysiology of cardiac tamponade and its clinical signs.…”
Section: Discussionmentioning
confidence: 80%
“…[1][2][3][4][5][6][7][8][9][13][14][15] The present study demonstrates distinctive hemodynamic features and echocardiographic manifestations of experimental cardiac tamponade in the presence of ischemic left ventricular dysfunction. The absence of pulsus paradoxus and the altered manner in which the cardiac chambers are compressed aid our understanding of the pathophysiology of cardiac tamponade and its clinical signs.…”
Section: Discussionmentioning
confidence: 80%
“…41 In the presence of cardiac tamponade, there is diastolic collapse of the free walls of the right atrium and/or right ventricle. 42,43 This is due to compression of these relatively low-pressure structures by the higher-pressure pericardial effusion. The collapse is exaggerated during expiration when right heart filling is reduced.…”
Section: Echocardiographymentioning
confidence: 99%
“…A large eVusion with a circumferential echo space of > 1 cm anteriorly or posteriorly is reported to be a powerful predictor of the development of tamponade. 3 Nevertheless, cardiac tamponade is usually a clinical diagnosis which is confirmed by echocardiography, where right ventricular (or right atrial) collapse is usually observed [4][5][6][7] ; however, left ventricular collapse is also seen, especially in the more advanced stages of tamponade, 8 and following cardiac surgery. 9 Rarely, despite life threatening tamponade, right atrial or right ventricular diastolic collapse may not be present in some patients, particularly following cardiac surgery.…”
Section: Discussionmentioning
confidence: 99%